El consentimiento implícito desde la jurisprudencia arbitral: comentarios a la primera sección del artículo 14 de la Ley de Arbitraje y algunas consideraciones vinculadas - Alvarado Giraldo, Jorge (2020)
The first scenario of article 14 of Legislative Decree 1071 positivizes the theory of the incorporation of non-signatory parties, know internationally as “implicit consent” theory. Although more than twelve years have elapsed since its publication, article 14 has remained disregarded by local pronouncements thus far from the arbitration or judicial levels that could provide us with more elements regarding its application in specific cases. This article aims to identify the way in which international arbitration tribunals have applied the implicit consent theory to determine what type of conducts throughout the contractual iter have justified the incorporation of a non-signatory to the arbitration. Moreover, the authors seek to provide answers to some questions of substantive and procedural nature: Is the non-signatory jointly and severally liable? How does the incorporation of a non-signatory remain consistent with their right to participate in the constitution of the arbitral tribunal? When should the incorporation of a non-signatory be decided?